"This Lady, She's A-List!": The Empowerment Impact of Womxn Political Elites for Womxn in South African Higher Education. (18th February 2020) - Michalko, Ján
Abstract: This article analyzes the norms that are expected of womxn political elites as role models, to further advance the research on the contributions of womxn in politics to womxn's empowerment. Based on interviews and group discussions with womxn at the University of Johannesburg, South Africa, it is argued that womxn in politics contribute to the students' normative construction of their ideal self and hence to their empowerment. Consequently, it is suggested that development interventions focus on womxn in politics as fully embedded in wider normative structures while also exposing womxn to a diverse group of womxn in power.